2022
DOI: 10.1107/s2414314622003649
|View full text |Cite
|
Sign up to set email alerts
|

Bis(oxotremorine) fumarate bis(fumaric acid)

Abstract: The title compound, bis(oxotremorine) fumarate bis(fumaric acid) {systematic name: 1-[4-(2-oxopyrrolidin-1-yl)but-2-ynyl]pyrrolidinium (2E)-but-2-enedioate bis[(2E)-but-2-enedioic acid]}, 2C12H19N2O+·C4H2O4 2−·2C4H4O4, has a single oxotremorine monocation protonated at the pyrrolidine nitrogen, one fumaric acid molecule and half of a fumarate dianion in the asymmetric unit. The ions and fumaric acid molecules are held together by N—H...O and O–H-...O hydrogen bonds in 40-membered rings with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This includes the zwitterionic natural product baeocystin (Naeem, Sherwood et al, 2022), its metabolite norpsilocin as both its freebase and fumarate (Chadeayne et al, 2020b), and its synthetic prodrug 4-acetoxy-N-methyltryptamine as a chloride salt (Glatfelter et al, 2022b). The remaining three are N-methylserotonin hydrogen oxalate (Naeem, Anas et al, 2023), 4-benzyloxy-N-isopropyltryptammonium chloride and 4-hydroxy-N-isopropyltryptamine (Laban et al, 2023) There are only four structures of freebase tryptamines known without indole substitution: the natural products tryptamine (Nowell et al, 2002) and N,N-dimethyltryptamine (Falkenberg, 1972), as well as N-methyl-N-propyltryptamine (Chadeayne et al, 2019b), and 3-[2-(piperidin-1-yl)ethyl]-1Hindole (Sahoo et al, 2020), while many other tryptamine freebases have been reported including serotonin .…”
Section: Database Surveymentioning
confidence: 99%
“…This includes the zwitterionic natural product baeocystin (Naeem, Sherwood et al, 2022), its metabolite norpsilocin as both its freebase and fumarate (Chadeayne et al, 2020b), and its synthetic prodrug 4-acetoxy-N-methyltryptamine as a chloride salt (Glatfelter et al, 2022b). The remaining three are N-methylserotonin hydrogen oxalate (Naeem, Anas et al, 2023), 4-benzyloxy-N-isopropyltryptammonium chloride and 4-hydroxy-N-isopropyltryptamine (Laban et al, 2023) There are only four structures of freebase tryptamines known without indole substitution: the natural products tryptamine (Nowell et al, 2002) and N,N-dimethyltryptamine (Falkenberg, 1972), as well as N-methyl-N-propyltryptamine (Chadeayne et al, 2019b), and 3-[2-(piperidin-1-yl)ethyl]-1Hindole (Sahoo et al, 2020), while many other tryptamine freebases have been reported including serotonin .…”
Section: Database Surveymentioning
confidence: 99%